Bronchiolitis obliterans as a long‐term sequela of Stevens–Johnson syndrome and toxic epidermal necrolysis in children. (17th July 2019) - Seccombe, E. L.; Ardern‐Jones, M.; Walker, W.; Austin, S.; Taibjee, S.; Williams, S.; Hossain, P.; Shenoy, D.; Fityan, A.
Summary: Toxic epidermal necrolysis (TEN) and Stevens–Johnson syndrome (SJS) are characterized by widespread skin and mucosal blistering and necrosis. The triggers and long‐term sequelae in children may differ from those reported for adults. Bronchiolitis obliterans (BO) is an uncommon complication, with only 15 previously reported cases, but can lead to significant long‐term morbidity, requiring lung transplantation in some cases. We report three children with nondrug‐related SJS ( n = 1) and TEN ( n = 2) who developed BO. Two were treated with intravenous immunoglobulin therapy (2–2.4 g/kg) and all three survived. We highlight salient learning points from our cases and potential pitfalls in diagnosis of BO, including delayed onset, and we also review the literature.